A inter-relação entre memória operacional e apraxia de fala - Martins, Fernanda Chapchap [UNIFESP] (2006)
To verify the interference of working memory in the apraxia of speech and explore which components of this memory would be involved in the motor planning of speech. Methods: There were assessed 22 apraxic subjects and 22 control subjects. There were administered a comprehension test and a protocol used to assess and classify the degree of apraxia of speech. To investigate working memory in the subjects, digit span forward and backward test, and a short-lenght and long-lenght word repetition test, both able to assess the phonoarticulatory loop, and the Rey Auditory Verbal Learning Test, which investigates both the phonoarticulatory loop and the episodic buffer, were administered. Results: The statistical analysis of the study showed some significant differences. The apraxic subjects performances in the memory tests, in the forward and backward digit span test, as well as in the short-lenght and long-length word repetition test, and in the Rey Auditory Verbal Learning Test was statistically significantly lower than the performance of the control group. It was also emphasized that the performance among the apraxic subjects in all of the memory tests was similar, independently on the degree of the apraxia. Conclusion: From the results mentioned earlier, the study concluded that subjects with apraxia of speech present a working memory deficit and that this deficit is more related to the articulatory process of the phonoarticulatory loop. Furthermore, a degree of compromise in the working memory deficit shown by the apraxic subjects is independent from the degree of apraxia of speech in these individuals.